1996
DOI: 10.1007/bf01809854
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of volcanic ash-gas clouds in the Earth's prebiotic chemistry

Abstract: Volcanic ash-gas clouds represent versatile local atmospheric environments appropriate for abiotic synthesis of rather complex organic molecules due to the simultaneous presence of various gaseous reagents, catalytically active inorganic particles, electric discharges, pressure and temperature gradients. They are relatively readily attainable for the scientists, contrary to objects or events of space origin (interstellar and planetary dust, meteoritic/cometary impacts, etc.), providing excellent opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…Theoretical approaches have shown that thermodynamic conditions of volcanic‐hydrothermal fluid reservoirs are consistent with those required for abiogenic synthesis of organic compounds [ Shock , 1990; Symonds and Reed , 1993; Wahrenberger , 1997; Shock and Schulte , 1998; Zolotov and Fegley , 1999; Zolotov and Shock , 2000; Wahrenberger et al , 2002]. Formation of abiogenic hydrocarbons was proposed to occur in a range of natural environments in the Earth's crust [ Seward , 1974; Abrajano et al , 1988; Szatmari , 1989; Isidorov et al , 1990; Sugisaki and Mimura , 1994; Kenney , 1995; Basiuk and Navarro ‐ González , 1996; Berndt et al , 1996; Giggenbach , 1997; Salvi and Williams ‐ Jones , 1997; Gize , 1999; Kelley and Früth ‐ Green , 2001; Sherwood Lollar et al , 2002; Taran et al , 2002; Taran and Cienfuegos , 2008; Etiope et al , 2011]. However, reliable geochemical parameters able to unequivocally identify abiogenic hydrocarbons in natural fluids have still not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical approaches have shown that thermodynamic conditions of volcanic‐hydrothermal fluid reservoirs are consistent with those required for abiogenic synthesis of organic compounds [ Shock , 1990; Symonds and Reed , 1993; Wahrenberger , 1997; Shock and Schulte , 1998; Zolotov and Fegley , 1999; Zolotov and Shock , 2000; Wahrenberger et al , 2002]. Formation of abiogenic hydrocarbons was proposed to occur in a range of natural environments in the Earth's crust [ Seward , 1974; Abrajano et al , 1988; Szatmari , 1989; Isidorov et al , 1990; Sugisaki and Mimura , 1994; Kenney , 1995; Basiuk and Navarro ‐ González , 1996; Berndt et al , 1996; Giggenbach , 1997; Salvi and Williams ‐ Jones , 1997; Gize , 1999; Kelley and Früth ‐ Green , 2001; Sherwood Lollar et al , 2002; Taran et al , 2002; Taran and Cienfuegos , 2008; Etiope et al , 2011]. However, reliable geochemical parameters able to unequivocally identify abiogenic hydrocarbons in natural fluids have still not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The specialist literature on the origin of life and molecular evolution contains many ideas and experimental data that link up nicely with the above literature from the chemical industry and mineralogy: early solar system (118); carbonaceous chondrites (119,120); heavy meteorite bombardment (121,122); geological setting of earliest life forms (123); ancient sediments (124,125); hot springs and oceans (126,127); prebiological activity in volcanic processes (128,129); alteration of obsidian to zeolites (130); adsorption of small molecules, including amino acids and growth of peptide chains, on macroporous silica (131-136); asymmetric adsorption by quartz (137); synthesis of amino acids on X-and Y-type faujasite zeolites (138); energy from feldspar and silica radioactivity and strain (139); heterogeneous chemistry on minerals (140); synthesis of oligopeptides with Beta, mordenite, faujasite, and kaolinite (141); models for prebiotic synthesis of RNA on aluminous zeolites (142) and montmorillonite (143); binding of adenine to montmorillonite and hydroxylapatite (144); instability of adenine in water (145); possible role of catalytic RNA (146-151); molecular replication (152); in vitro evolution of nucleic acids (153); origin and amplification of biomolecular chirality (154); chiral symmetry breaking during self-assembly of monolayers from chiral purine (155); kinetic cooperativity in prebiotic catalysts (156); crucial stages in origin of animate matter (157); and sequence of biological chirality (158).…”
mentioning
confidence: 91%
“…Comparison of terrestrial atmospheric electrical parameters in fair weather, thunderclouds and volcanic plumes (afterBasiuk and Navarro-Gonzá lez 1996) …”
mentioning
confidence: 99%